A two-level game optimal dispatching model for the park integrated energy system considering Stackelberg and cooperative games. (September 2021) - Yang, Shenbo; Tan, Zhongfu; Zhou, Jinghan; Xue, Fan; Gao, Hongda; Lin, Hongyu; Zhou, Feng'ao
Highlights: A two-layer game interaction framework is constructed. The upper layer is a Stackelberg game, and the lower layer is a cooperative game. A two-layer decision optimization model is constructed. The Stackelberg game is based on maximum net income as the objective function. The income allocation model is constructed in the lower layer. Abstract: Due to the reform and liberalization of the multi-energy market and the increasing complexity of the internal main body coupling of the park integrated energy system, the effective use of the external multi-energy market and the flexible participation of internal multiple subjects to compensate for the shortage of supply in the park integrated energy system has practical research significance. Therefore, in this paper, a two-layer game model was constructed to optimize the park integrated energy system internally and externally. Firstly, an upper-level Stackelberg game model of the superior energy network and park system was constructed to carry out external optimization of the park integrated energy system. Second, a cooperative game model was constructed for the park users, the gas supply system, and the park integrated energy system to undertake internal optimization of the park integrated energy system. In addition, a multi-agent cooperative game benefit distribution model was constructed based on the Shapley value method, the Banzhaf value method, the solidarity value method, and the improved risk factor. Finally, multiple scenarios were established and the solution was optimized using a two-stage solution algorithm. The results show that cooperation between users, the gas supply system, and the park integrated energy system of the lower-level park can improve the internal supply and demand matching of the park integrated energy system, and enhance its competitiveness in the upper Stackelberg game.